Confidentiality and public policy in alternative dispute resolution - Ansari, Abdul Haseeb; Khan, Assaduzzaman; Ahmad, Muhamad Hassan (CLJ Publication, 2020)
One of the debatable issues in alternative dispute resolution (ADR) processes is the extent to which the proceedings, written or unwritten, has to be kept confidential by the parties to the dispute and the mediator or arbitrator, as the case may be, and statement(s) given by third parties or amicus curiae, especially in international arbitration. The US law on dispute settlements by courts contemplates the law to be sparse. But if disputes are to be settled by mediation, arbitration, negotiation or by any other alternative means of dispute resolution, the need to preserve the confidentiality of proceedings becomes pressing. It is because in a subsequent court case, any of the disputing parties may wish to use the proceedings of any previous ADR mechanism, or the mediator, for instance, who failed to bring the parties to an agreement may be asked to uncover the reason for the failure of the ADR. This is more so in multi-party disputes. On the other hand, some information of purely commercial or economic nature from the proceeding should be allowed to be used in later court cases, unless something personal or otherwise is implicated. This will make the judicial proceedings closer to justice. In view of this, it is said that it is better for the disputing parties to enter into a confidentiality agreement to be signed also by the arbitrator or negotiator as the case may be. It may be an ADR agreement, or separate, entered into simultaneously between the disputing parties or at a later stage. The confidentiality in ADR has also been the subject matter of state policies, law and judicial delineations. They also emphasise on the importance of confidentiality in the ADR mechanism of dispute resolution with few exceptions. The Guidelines of the Administrative Appeals Tribunal of Australia and the Singapore law on arbitration and mediation are worth referring in this respect. International law is mainly there in the rules developed by the International Court of Arbitration under the International Chamber of Commerce. International courts and centres around the world have also developed rules for resolving disputes on the basis of ADR. International law is also enshrined in the International Covenant on Civil and Political Rights (ICCPR) and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) by implication, demonstrate confidentiality to be maintained in the situations of sexual harassment, rape, infertility and any other genetic infirmity or disease. If they are part of the any ADR mechanism, they have to be kept confidential by laws enacted by the member states. Likewise, any family genetic deficiency, disparity, disease or infirmity has to be protected under ICCPR. It may be noted here that many states have personal data protection laws to enforce it. They too, in turn, strive to maintain confidentiality in judicial and ADR proceedings.